The Effect of Nickel and Aluminum Concentration on Cyclic Oxidation Resistance of Mild Steel (AISI 1020) - Yahya Salman; Mahmood Hmood; edrees ghadeer (College of Education for Pure Sciences, 2020)
Experimental studies have been made to determine the oxidation be heavier of several coatings system on commercial mild steel alloy (AISI 1020). The oxidation kinetics of a single stage coating such as Aluminized and Nickel have been  under )1000°C( using a thermal cyclic oxidation.The structures were studied using optical microscope to identify a phases. Most coating use to enhance the formation of protective oxid scale, in this research, the results for Nickel coating  showed some reduction in resistance of )AISI 1020( alloy and It is found they  follow linear rate law, but Aluminized coating using a pack - cementation technique, exhibited the greatest resistance to oxidation, followed parabolic law (protective oxidation behavior). because it has a good ductility and its capability to form a protective oxid Layer )Al2O3(, such Alumina scale is known as thermally and electrically insulator and characterized with slow gowning rate.